2008
DOI: 10.1101/lm.825008
|View full text |Cite
|
Sign up to set email alerts
|

Reconsolidation of appetitive memories for both natural and drug reinforcement is dependent on β-adrenergic receptors

Abstract: We have investigated the neurochemical mechanisms of memory reconsolidation and, in particular, the functional requirement for intracellular mechanisms initiated by ␤-adrenergic signaling. We show that propranolol, given in conjunction with a memory reactivation session, can specifically disrupt the conditioned reinforcing properties of a previously appetitively reinforced conditioned stimulus (CS), whether the stimulus had been associated with self-administered cocaine or with sucrose. These data show that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
172
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(191 citation statements)
references
References 45 publications
13
172
6
Order By: Relevance
“…ANOVA revealed a significant effect of chamber during the CPP trial (F 2,20 ¼ 18.58, po0.001), but post hoc analyses indicated that an equivalent amount of time was spent in the previously propranolol-and saline-paired chambers (p40.05). Thus, propranolol did not generate an affective state sufficient to induce a CPP or aversion, consistent with previous findings (Milton et al, 2008). We also evaluated the effects of propranolol on locomotor activity.…”
Section: Propranolol Prevents Retrieval Of a Cpp When Administered Besupporting
confidence: 68%
“…ANOVA revealed a significant effect of chamber during the CPP trial (F 2,20 ¼ 18.58, po0.001), but post hoc analyses indicated that an equivalent amount of time was spent in the previously propranolol-and saline-paired chambers (p40.05). Thus, propranolol did not generate an affective state sufficient to induce a CPP or aversion, consistent with previous findings (Milton et al, 2008). We also evaluated the effects of propranolol on locomotor activity.…”
Section: Propranolol Prevents Retrieval Of a Cpp When Administered Besupporting
confidence: 68%
“…with either 10 mg/kg of propranolol or saline and tested again 48 h later (Test 2). This dosage of propranolol is one of the highest previously used in several studies to interfere with the consolidation or reconsolidation in several different types of memories, including both aversive and appetitive (e.g., Sara et al 1995;Przybyslawski et al 1999;Saber and Cain 2003;Debiec and LeDoux 2004;Diergaarde et al 2006;Abrari et al 2007;Milton et al 2008;Rodriguez-Romaguera et al 2009). All groups of rats had similar retention latencies at Test 1 and Test 2.…”
Section: Resultsmentioning
confidence: 99%
“…For example, LaLumiere et al (2010) found that repeated post-training administration of the b2-adrenergic agonist clenbuterol within the infralimbic cortex enhanced retention of extinction, as evidenced by lower responding in subsequent sessions. Other past work has found that interference with the NE system can disrupt stable memory formation as post-retrieval administration of propranolol can impair cocaine-conditioned place preference (Bernardi et al, 2006(Bernardi et al, , 2009Fricks-Gleason and Marshall, 2008) or conditioned reinforcement (Milton et al, 2008). These effects have been attributed to disrupted reconsolidation.…”
Section: Learning Consolidation and Reconsolidationmentioning
confidence: 99%